Fabrication of chemical patterns from graphoepitaxially assembled block copolymer films by molecular transfer printing - Jin, Xiaosa; Zhang, Xiaosa; Wan, Lei; Nealey, Paul F.; Ji, Shengxiang (Polymer (Guilford), 2014)
Fabrication of chemical patterns by electron beam lithography or extreme ultraviolet interference lithography is either low-throughput or prohibitively expensive to practice at sub-50 nm feature dimension. Here we report a new high-throughput approach that combines the advantages of both graphoepitaxy and molecular transfer printing (MTP) to fabricating chemical patterns at low cost for directed assembly of block copolymers. In this new approach, a cylinder-forming block copolymer ternary blend film is directed to assemble on a topographic HSQ substrate with sub-Lo, where Lo is the natural period of the block copolymer, relief structures to increase the feature density by a factor of ∼20, the surface domain pattern is replicated using MTP to create 1:1 chemical pattern, and then a lamellae-forming block copolymer is directed to assemble on the chemical pattern to realize high-aspect ratio Manhattan type nanostructures. This combined strategy allows us to fabricate chemical patterns with feature dimension below the resolution limit of current lithographic tools. [Display omitted]